PROFESI SEBAGAI UKURAN KAFA’AH DALAM PERNIKAHAN BAGI MASYARAKAT KECAMATAN JAYA KABUPATEN ACEH JAYA - Aria Sandra; Nyak Miftahul Rezki (SYARIAH: Journal of Islamic Law, 2021)
With the existence of kafa'ah in marriage, it is hoped that each candidate will be able to get harmony and harmony. The existence of various considerations on these problems is intended so that in married life there are no inequalities and incompatibility. From this background, the writer formulates the problem as follows, namely 1. how are the views of the people of Jaya District, Aceh Jaya Regency towards the profession as an element of kafa'ah in marriage, 2. What are the factors behind the profession as a measure of kafa'ah in marriage, 3. What are the guidelines for the Jaya community, Aceh Jaya Regency in determining the profession as an element of kafa'ah in marriage. This study uses a descriptive qualitative research method, namely a method that examines a condition, a thought or an event in the present, factual and accurate regarding the facts, properties and relationships between the phenomena being investigated, referring to the relevant literature. Research by collecting theoretical data through the library by reading books, books and internet articles. The people of Jaya Subdistrict, Aceh Jaya Regency in general are very considerate of kafa'ah itself, due to differences in educational background, work, organization and others.